Pharmacokinetics of Naja sumatrana (Equatorial Spitting Cobra) Venom and Its Major Toxins in Experimentally Envenomed Rabbits - Yap, Michelle Khai Khun (Public Library of Science, 2014)
BACKGROUND: The optimization of snakebite management and the use of antivenom depend greatly on the knowledge of the venom's composition as well as its pharmacokinetics. To date, however, pharmacokinetic reports on cobra venoms and their toxins are still relatively limited. In the present study, we investigated the pharmacokinetics of Naja sumatrana (Equatorial spitting cobra) venom and its major toxins (phospholipase A(2), neurotoxin and cardiotoxin), following intravenous and intramuscular administration into rabbits. PRINCIPAL FINDINGS: The serum antigen concentration-time profile of the N. sumatrana venom and its major toxins injected intravenously fitted a two-compartment model of pharmacokinetics. The systemic clearance (91.3 ml/h), terminal phase half-life (13.6 h) and systemic bioavailability (41.9%) of N. sumatrana venom injected intramuscularly were similar to those of N. sputatrix venom determined in an earlier study. The venom neurotoxin and cardiotoxin reached their peak concentrations within 30 min following intramuscular injection, relatively faster than the phospholipase A(2) and whole venom (T(max) = 2 h and 1 h, respectively). Rapid absorption of the neurotoxin and cardiotoxin from the injection site into systemic circulation indicates fast onsets of action of these principal toxins that are responsible for the early systemic manifestation of envenoming. The more prominent role of the neurotoxin in N. sumatrana systemic envenoming is further supported by its significantly higher intramuscular bioavailability (F(i.m.) = 81.5%) compared to that of the phospholipase A(2) (F(i.m.) = 68.6%) or cardiotoxin (F(i.m.) = 45.6%). The incomplete absorption of the phospholipase A(2) and cardiotoxin may infer the toxins' affinities for tissues at the injection site and their pathological roles in local tissue damages through synergistic interactions. CONCLUSION/SIGNIFICANCE: Our results suggest that the venom neurotoxin is absorbed very rapidly and has the highest bioavailability following intramuscular injection, supporting its role as the principal toxin in systemic envenoming.